Nationwide survey of ticks on domesticated animals in Taiwan: Revealing the hidden threat to animal and public health - Liao, Jhih‐Rong; Liao, Yi‐Hao; Liao, Kuei‐Min; Wu, Huai‐Hui; Tu, Wu‐Chun; Lin, Ying‐Hsi (Medical and veterinary entomology, 2024)
Ticks are not only bloodsucking ectoparasites but also important vectors of tick‐borne diseases (TBDs), posing significant threats to public and animal health. Domesticated animals serve as critical hosts for numerous ticks, highlighting the importance of understanding tick infestations in Taiwan. To address this knowledge gap, we conducted a nationwide survey to identify ticks on domesticated animals and associated environments in 2018 and 2019. A total of 6,205 ticks were collected from 1,337 host animals, revealing the presence of seven tick species, with Rhipicephalus microplus, and Rhipicephalus sanguineus being the dominant species. High infestation rates and widespread distribution of ticks were observed on domesticated animals, especially on dogs and cattle (yellow cattle and angus cattle), and the neighbouring grassland of yellow cattle. While this study has certain limitations, it provides valuable insights into the distribution and prevalence of ticks on domesticated animals in Taiwan and their implications for controlling TBDs. Further research is needed to comprehensively understand the complex interactions among ticks, hosts and pathogens. Seven tick species were identified in Taiwan through a nationwide survey of domesticated animals, providing valuable information on the diversity of ticks. The distribution of ticks on domesticated animals in Taiwan was documented, serving as a crucial baseline for understanding the epidemiology of tick‐borne diseases (TBDs) in the future. The findings of this study contribute to the knowledge of tick ecology and potential TBD risks in Taiwan, highlighting the importance of tick surveillance and management measures to address the issues of both public health and animal health.